Self-cleaning, photocatalytic films on aluminum plates for multi-pollutant air remediation: promoting adhesion and activity by SiO2 interlayers. (1st September 2021) - Cionti, Carolina; Cosaert, Ewoud; Deshayes, Gabriele; Falletta, Ermelinda; Meroni, Daniela; Bianchi, Claudia L; Poelman, Dirk
Abstract: In recent years, nanoparticles have come under close scrutiny for their possible health and environmental issues, making them less attractive for photocatalytic applications in air or water purification. Replacing free nano-powders with active and stable films is thus a fundamental step towards developing effective photocatalytic devices. Aluminum represents a cheap and technologically-relevant substrate, but its photocatalytic applications have been hampered by adhesion issues and metal ion diffusion within the photocatalytic layer. In this work, the use of silica interlayers is investigated as a strategy to promote adhesion, efficiency and reusability of TiO2 films deposited on aluminum plates. Films were prepared from stable titania sols to avoid the use of nano-powders. Aluminum substrates with different surface morphology were investigated and the role of the silica interlayer thickness was studied. Films were extensively characterized, studying their structure, morphology, optical properties, adhesion and hardness. Self-cleaning properties were studied with respect to their superhydrophilicity and ability to resist fouling via alkylsilanes. Photocatalytic degradation tests were carried out using both volatile organic compounds and NO x, also in recycle tests. The presence of the silica interlayer proved crucial to promote the film robustness and photocatalytic activity. The substrate morphology determined the optimal interlayer thickness, especially in terms of the film reusability.